Estate youth and complicated migration in Malaysia's oil palm plantations: the emotions of leaving and connecting back - Chakraborty, Kabita; Thambiah, Shanthi; Arumugam, Janarthani (Taylor & Francis, 2018)
This paper investigates the emotional relationship young Tamil Indians have with oil palm plantations they are leaving behind or have left behind. Working in a small town in Malaysia, as well as in a large estate, we show how communal and individual aspirations of migration shape young people's mobility. While young people recognize the poverty and marginalization of plantation life, they continue to be emotionally and affectually connected to plantations through socio-cultural and spiritual practices. Post-migration we show how youth maintain estate connections, and argue that the pull back towards plantations is contrary to state-sponsored ideologies of modernization. Not all young people feel the same pull; many try to distance themselves from their estate roots through consumption and other social practices. Responding to calls for researchers emotions to be present in youth research, the paper also briefly reflects how adult emotions shape our understanding of young people's emotions of migration.